(untitled) (Research, Society and Development, 2025)
The study aimed to analyze the enrollment period of newcomers in fitness centers in Petrolina-PE according to sex and age group for eight years. 5,135 individuals participated in the study, 2,095 men and 3,040 women, aged between 18 and 75 years old, classified as sedentary and apparently healthy. The subjects were allocated into seven groups (G1 = <20 years; G2 = 20 to 29 years; G3 = 30 to 39 years; G4 = 40 to 49 years; G5 = 50 to 59 years; G6 = 60 to 69 years and G7 => 70 years). Between 2009 and 2016, the year with the highest demand for fitness centers was 2012 with 1,157 new enrollments, while 2009 was the lowest year with 370 new students. The months of greatest student adherence were January, July and October, while February, June and December had the lowest number. The groups aged 20 to 29 and 30 to 39 years old were the ones who most sought physical training environments, followed by those under 20 years old. It was concluded that the months corresponding to the vacations had a greater adhesion of enrollments in the gyms, in which women and younger people, between 20 and 29 years old, showed greater interest in practicing physical exercise. In addition, the months of February, June and December, considered festive months, had the lowest number of entrants, and these showed less interest in physical activity with age.